Coexistence of Post-traumatic Growth and Post-traumatic Depreciation in the Aftermath of Trauma: Qualitative and Quantitative Narrative Analysis - Zięba, Mariusz; Wiecheć, Katarzyna; Biegańska-Banaś, Joanna; Mieleszczenko-Kowszewicz, Wiktoria (Frontiers in Psychology, 2019)
Objectives: Post-traumatic growth (PTG) and post-traumatic depreciation (PTD) can be defined respectively as positive and negative changes in the aftermath of trauma. These changes can be assigned to the following domains: personal strength, relating to others, new possibilities, appreciation of life, spiritual and existential change. The aim of this study was to explore the possibility that positive and negative effects of trauma can coexist and explore the categories of effect. Methods: 72 participants were asked to recount their experience of trauma and answer questions about how it had affected their thinking about themselves and the world. Participants’ narratives were analyzed by competent judges and using Linguistic Inquiry and Word Count. Results: The domains in which positive changes were most frequently observed were Personal Strength (26.09%), Relating to Others (24.22%), and Appreciation of Life (21.12%). Negative changes mainly affected Relating to Others (33.33%) and Personal Strength (23.33%). The results were confirmed by quantitative analysis of narratives: participants’ narratives of trauma and its consequences contained more words which expressing positive emotions (1.67%) than negative emotions (.90%), paired-sample t(60) = 9.70, p < .001. There were correlations between the frequency of words referring to positive emotions and PTG, r(62)=0.39, p<.01, and between the frequency of words referring to negative emotions and PTG, r(62)=0.23, p<.05. Conclusions: PTG and PTD can coexist and they can be regarded as outcomes of two separate processes. The study results also suggest that although PTG and PTD can coexist they may be considered different domains of psychological functioning.